Effect of Intracameral Cefuroxime on Graft Endothelial Cells in Descemet Membrane Endothelial Keratoplasty: A Comparative Study. (3rd July 2021) - Ghazal, Wassim; Saad, Alain; Courtin, Romain; Gatinel, Damien; Panthier, Christophe
ABSTRACT: Purpose : To evaluate the effect of intracameral cefuroxime on graft endothelial cell loss after simple Descemet Membrane Endothelial Keratoplasty (DMEK) and combined DMEK and cataract surgery. Materials and Methods : Single-center retrospective comparative analysis. One hundred and three patients were included, 31 in the cefuroxime group and 72 in the non-cefuroxime (NC) group. Best Spectacle-Corrected Visual Acuity (BSCVA), endothelial cell density (ECD) of the graft measured by specular microscopy, and the recipient's pachymetry were recorded pre-operatively and at 1, 3, and 6 months after surgery. Results : In the cefuroxime group, BSCVA was 0.22 ± 0.27 LogMAR, 0.15 ± 0.24 LogMAR and 0.07 ± 0.22, respectively, at 1, 3, and 6 months after surgery with no significant differences found when compared to the NC group ( p > .05). Anatomical outcomes were similar as mean pachymetry decreased from 599 ± 51 µm preoperatively to 511 ± 30 µm at 6 months after surgery in the cefuroxime group and from 607 ± 67 µm preoperatively to 519 ± 32 µm at 6 months in the NC group ( p = .25). Endothelial cell loss was comparable between both groups: 33.4% versus 33.6% at 1 month ( p = .97), 37.4% versus 34.9% at 3 months ( p = .68) and 41.6% versus 38.3% at 6 months ( p = .42) in the cefuroxime and NC groups, respectively. The rates of rebubbling, graft rejection, and cystoid macular edema were not significantly higher in the cefuroxime group. Conclusion : The use of intracameral cefuroxime during simple or combined DMEK did not lead to higher graft endothelial cell loss.